Panorama de atuação dos Centros Dia para Pessoas Idosas na Região Metropolitana de São Paulo - Semensato, Carolina Ramos (Universidade Federal de São Carlos, 2025)
In response to the growing and accelerated phenomenon of population aging, care services for elderly people are gaining prominence. Day Care Centers for the Elderly (CDIs) are characterized as day care services of medium complexity within the special social protection network for elderly people with reduced frailty and support for their families. This service denotes social relevance for partial care and in the state of São Paulo they are considered socio-sanitary services. Managers are expected to understand the services assigned to these spaces, acting in accordance with current legislation. Objective: To investigate the operating system of CDIs in the São Paulo Metropolitan Region (RMSP) and identify whether the institutional routine is compatible with current regulations. Study design: Qualitative, quantitative, exploratory and descriptive research. The analysis is based on the fundamentals of thematic content in the light of the theoretical framework and categorization. The study was carried out in stages: 1-documentary organization; 2-bibliographic review using the following descriptors: frail elderly, ageing, day-center, social support, health planning and social assistance, in the following databases: Latin American Literature in Health Sciences, Scientific Electronic Library Online, Online Medical Literature Search and Analysis System; 3-mapping of CDIs in the RMSP through active search, a list provided by the partners (1. São Paulo State Secretariat for Social Development, 2. São Paulo Day-Center Forum and 3. Application of a semi-structured online questionnaire to CDI managers about the characterization of the service, the public profile, the correspondent, the team and the routine; and Stage 5. Data analysis. All research ethics principles were applied. Results: Stage 1: Approval by the Research Ethics Committee/UFSCar and agreement from the partners. Stage 2: 48 scientific publications were identified, of which we excluded 6 duplicates and 36 for thematic incompatibility, resulting in 6 publications in line with the theme. There was a lack of publications dealing specifically with the panorama of ICD work and legislation, i.e. a subject that has been little explored. The studies provide a theoretical framework on the social contributions of ICDs, the relationship between social support and BADL, the financial management of services and day care in relation to the ageing population. Stage 3: The mapping resulted in a total of 158 services belonging to the RMSP, which were categorized into three groups: 1.CDI (49; 31%); 2.CD and similar (55; 34.8%) and 3.ILPI/CDI (54; 34.2%). Stage 4: Of the 158 services mapped, 18 could not be contacted and 5 declined to participate. The sample for data collection via online questionnaire was 135 services. They were sent out between September and November 2024, in 3 attempts to participate. Data analysis: (article 2) There were 10 responses, however, 3 services did not correspond to ICDs and were excluded. Sample of 7 participating CDIs, 5 non-governmental and 2 governmental. Profile of service users: 73.6% were women, with an average age of 80, widowed, with a functional profile of II and who attended the service five days a week. Most of the people looking for a place were family members looking to socialize and the admission process is based on a health and functionality assessment. The profile of the managers is female, average age 43, married (57.1%) with a postgraduate degree. The teams are predominantly female with an average age of 43. 50.43% of the employees have higher education in biopsychosocial areas, the majority of whom are hired under the Consolidation of Labor Laws. All the CDIs operate 5 times a week for an average of 12 hours a day, with 57.14% offering four meals. The activities carried out are physical and cognitive stimulation. Conclusion: The internationalization of the 6 studies identified shows the scarcity of relevant publications on the subject in the Brazilian context and reveals the social bias of this research. In addition, there are discrepancies between the data available on official websites about ICD services. This information is scattered and fragmented, as there is no complete list. The results indicate that although the services are acting in accordance with the legislation, there may be weaknesses in the perception of managers, in addition to the need to expand the activities offered in line with the legislation, especially with regard to the integration of the community, the family and the health services. It should be noted that this study is of great (and pioneering) relevance and makes a mutual contribution to various sectors of society. It is hoped that it will encourage reflection on the organizational structures and work processes of ICDs, in line with legal technical standards, as well as highlighting measures for maintaining links and keeping older people included in the community.
Overview of the activities of Day Centers for the Elderly in the Metropolitan Region of São Paulo
Keywords: Assistência diurna; Idoso fragilizado; Envelhecimento; Centros Dia; Apoio social; Planejamento em saúde; Assistência social; CIENCIAS DA SAUDE; CIENCIAS BIOLOGICAS; CIENCIAS SOCIAIS APLICADAS::ADMINISTRACAO; OUTROS